The Pecking Order Theory: Evidence from Malaysia - Poon, Wei Leng (2009)
The pecking-order theory of capital structure, which predicts that firms prefer internal to external finance, is one of the most influential theories of corporate leverage. This study examines whether the Malaysian listed companies follow a pecking order from debt to equity. Using the entire cross-section sample of Malaysian listed companies in 2007, evidence is found to support that Malaysian listed companies follow a pecking order when they need funds to finance investment projects. Further subsample analyses indicate that medium-sized companies and large-sized companies follow a pecking order and small-sized companies do not. These results suggest that the Malaysian capital market is well-developed.